PERAN PEMBERDAYAAN DANA ZAKAT, INFAQ, DAN SHADAQAH DALAM MEMPERSIAPKAN TANTANGAN KEPEMIMPINAN INDONESIA - Teuku Ahmad Naufal; Karjadi Mintaroem (Jurnal Ekonomi Syariah Teori dan Terapan, 2018)
This study aims to determine the empowerment of zakat, infaq, and sadaqah (ZIS) in Yayasan Dana Sosial Al-Falah (YDSF) in Surabaya. The research was motivated by a crisis of leadership in the present, which is why it is necessary to have education of Islamic leadership early in student age. The education to prepare a leader is not cheap, and therefore it needs a solution in a way of help of zakat organizations. This is a qualitative research by case study strategy. The data collection was taken by doing data reduction, data presentation, andconclusion. The research results show that the empowerment of zakat, infaq, and sadaqah has an impact on the field of education with the establishment of RK program. RK does not only educate the participants to become candidates for leader, but also prepare them into Quran generation that is supported by a variety of activities and sharia-based leadership REFERENCESAbu & Supriyono Widodo. 2003. Psikologi Belajar. Jakarta: Rineka CiptaAkaha, Akhmad Zulfaidin. 2001. Psikologi anak dan remaja muslim. Jakarta Timur: Pustaka Al- KautsarAmiruddin Inoed, dkk. Anatomi Fiqh Zakat : Potret & Pemahaman Badan Amil ZakatSumatera Selatan. (Yogyakarta : Pustaka Pelajar, 2005), hlm. 13 (SUMBERNYA INFAQ dan SHADAQAH)Hafidhuddin, Didin. 2002. Zakat Dalam Perekonomian Modern. Jakarta : Gema InsaniHessel Nogi S,Tangkilisan. 2005. Manajemen Publik. Jakarta: PT GrasindoHusaini, Adian. 2015. Mewujudkan Indonesia Adil dan Beradab. Jakarta: Bina Walam dan INSISTMifctachul Huda. (2009). Pekerjaan Sosial dan Kesejahteraan Sosial:Sebuah Pengantar. Yogyakarta: Pustaka Pelajar.P3EI. 2008. Ekonomi Islam. Jakarta: Rajawali Press, hlm.54Qardhawi, Yusuf. 2007. Hukum Zakat. Jakarta: Lintera antar nusaRiyandono, Muhammad Nafik Hadi. 2008. Ekonomi ZISWAQ (Zakat,Infaq, Shadaqah, dan Wakaf). Surabaya: IFDI dan Cenforis.Suharto, Edi. 2009. Membangun Masyarakat Memberdayakan Rakyat. Bandung: PT. Refika Aditama